Pelatihan Dan Pendampingan Inovasi Produk Serta Kemasan Bagi Usaha Mikro Kecil Menengah (UMKM) Makanan Ringan Untuk Meningkatkan Volume Penjualan Wirausaha Di Kabupaten Simalungun - Augustinus Suryadi Sitanggang (Serat Acitya, 2022)
Community service activities are carried out in Raya villages in need, namely Raya Village, Raya District, Simalungun Regency. This activity is a collaboration between lecturers and Micro, Small and Medium Enterprises (UMKM) partners. The limitations of MSMEs in Raya Village, Simalungun Regency in their knowledge of innovating correct products and packaging and the desire to progress and develop are their main priorities in solving these problems. The problems that exist in the MSMEs of Raya Village include: finding solutions to existing problems by providing training and guidance as well as assistance during the product and packaging innovation process, providing complete assistance in innovating products and packaging as well as funds to help improve MSME products and packaging, assisting in the process of innovating MSME products and packaging to make them better. This assistance and coaching does not stop at training, but until the MSMEs can really run well. The team uses methods that will be implemented during the activity by sharing and assisting partners in innovating. The planned output is increased product sales from innovation in product packaging and labeling, as well as expanding the product market through online marketing.